2018
DOI: 10.1111/jvh.12917
|View full text |Cite
|
Sign up to set email alerts
|

Shortened therapy of eight weeks with paritaprevir/ritonavir/ombitasvir and dasabuvir is highly effective in people with recent HCV genotype 1 infection

Abstract: Paritaprevir/ritonavir/ombitasvir and dasabuvir with or without ribavirin for 12 weeks are approved for treatment of chronic HCV genotype 1 infection. This study assessed the efficacy of shortened duration paritaprevir/ritonavir/ombitasvir and dasabuvir with or without ribavirin for 8 weeks among people with recent HCV infection. In this open-label single-arm trial conducted in Australia, England and New Zealand, adults with recent HCV (duration of infection <12 months) received paritaprevir/ritonavir/ombitasv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…362 The combination of ritonavir-boosted paritaprevir, ombitasvir and dasabuvir administered for 8 weeks yielded a 97% (29/30; 1 non-virological failure) SVR rate in patients with recently acquired hepatitis C in the TARGET-3D study. 363 Finally, 6 weeks of treatment with glecaprevir/pibrentasvir yielded a 90% SVR12 rate (27/30; 1 virological failure) in patients with recently acquired hepatitis C. 364 In a multicentre international, open-label trial, patients with recently acquired hepatitis C were randomised into 2 groups to receive either 6 or 12 weeks of the fixed-dose combination of sofosbuvir and velpatasvir. Interim analysis results were presented from 127 of the planned 250 inclusions.…”
Section: Treatment Of Recently Acquired Hepatitis Cmentioning
confidence: 99%
“…362 The combination of ritonavir-boosted paritaprevir, ombitasvir and dasabuvir administered for 8 weeks yielded a 97% (29/30; 1 non-virological failure) SVR rate in patients with recently acquired hepatitis C in the TARGET-3D study. 363 Finally, 6 weeks of treatment with glecaprevir/pibrentasvir yielded a 90% SVR12 rate (27/30; 1 virological failure) in patients with recently acquired hepatitis C. 364 In a multicentre international, open-label trial, patients with recently acquired hepatitis C were randomised into 2 groups to receive either 6 or 12 weeks of the fixed-dose combination of sofosbuvir and velpatasvir. Interim analysis results were presented from 127 of the planned 250 inclusions.…”
Section: Treatment Of Recently Acquired Hepatitis Cmentioning
confidence: 99%
“…17 Another study reported comparable SVR12 results (97%; 29/30) following eight weeks of treatment with 3D AE RBV in HIV-positive patients with recent HCV infection. 18 Nevertheless, the optimal duration and outcome of IFN-free therapy in HIV/AHC remain unclear, since all conducted studies had heterogeneous inclusion criteria and suffered from small sample size. 19 Notably, previous data suggested that even a short duration of HCV infection might induce significant liver fibrosis and substantial liver damage in HIV-positive MSM, 20 underlining the urge to initiate treatment early.…”
Section: Introductionmentioning
confidence: 99%
“…The median time between diagnosis and treatment (15 weeks) was a little shorter than in our study, but the median VL (6.2 log 10 IU/mL) was higher and the median ALT (133 U/L) lower than in our study. Martinello et al [ 23 ] treated with 8 weeks of the no longer widely used regimen of paritaprevir/ritonavir/ombitasvir, dasabuvir, and ribavirin and cured all 23 HIV-infected participants. The median time between diagnosis and treatment (23 weeks) was the longest among these studies, although despite this longer time to treatment, the median HCV VL (5.7 log 10 IU/mL) and ALT level (~150 U/L) were about intermediate between the Naggie et al study and ours.…”
Section: Discussionmentioning
confidence: 99%